X-RAY IMAGING APPARATUS AND POSITIONING SUPPORT UNIT FOR X-RAY IMAGING APPARATUS - OKUMURA KOJI (2023)
To provide an X-ray imaging apparatus capable of easily adjusting relative angle relationships between a detection surface of an X-ray detection part and an X-ray irradiation direction of an X-ray irradiation part in addition to adjusting the position that an X-ray is radiated, and to provide a positioning support unit for the X-ray imaging apparatus.SOLUTION: An X-ray imaging apparatus 100 includes: an X-ray irradiation part 1; an X-ray detection part 2; an angle relationship detection part for detecting relative angle relationships between a detection surface 20 of the X-ray detection part 2 and an X-ray irradiation direction of the X-ray irradiation part 1; and a projection part for projecting an irradiation position marker indicating the position that an X-ray is radiated from the X-ray irradiation part 1 onto a body surface of a subject 101. The projection part changes a display mode of the irradiation position marker on the basis of a degree of deviation of the detected angle relationships with respect to a set angle that is set beforehand.SELECTED DRAWING: Figure 1 【課題】Ｘ線が照射される位置の調整に加えて、Ｘ線検出部の検出面とＸ線照射部のＸ線の照射方向との相対的な角度関係の調整を容易に行うことが可能なＸ線撮影装置、および、Ｘ線撮影装置用位置決め支援ユニットを提供することである。【解決手段】このＸ線撮影装置１００は、Ｘ線照射部１と、Ｘ線検出部２と、Ｘ線検出部２の検出面２０とＸ線照射部１のＸ線の照射方向との相対的な角度関係を検出する角度関係検出部と、Ｘ線照射部１からＸ線が照射される位置を示す照射位置標識を被検者１０１の体表面に投影する投影部と、を備える。投影部は、検出された角度関係の予め設定された設定角度に対するズレ度合いに基づいて、照射位置標識の表示態様を変更するように構成されている。【選択図】図１